ALUTA CONTINUA, OR CLOSING THE GENERATION GAP: SECTION 197 OF THE LRA AND ITS APPLICATION TO OUTSOURCING* - Craig Bosch (Obiter, 2022)
There has recently been a fair amount of debate around whether section 197 of the Labour Relations Act applies to so-called ‘second generation’ business transfers. The Labour Court has held that it can, provided the relevant business is transferred as a going concern. This article analyses and considers the correctness and desirability of that decision in light of the relevant statutory provisions, the proper approach to interpreting the provisions of the LRA, the practical consequences of the decision, the criticism that has been levelled at the decision and comparative law.